PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KESEJAHTERAAN KELUARGA DI SEKITAR TAMBANG - Nirmaya, Gilar Cahya; Muflikhati, Istiqlaliyah; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2014)
This research aimed to analyze the influence of Corporate Social Responsibility (CSR) program onfamily’s well-being in Batulicin mining area, South Kalimantan. This study applied a combination of cross-sectional andretrospective design. The data were collected in Sarigadung village. Samples in this study were poor families, whom distinguished by the benefits that received from CSR program. Samples were 70 families that selected purposively; half were identified as CSR program receiver families while other difined as nonreceiver family of CSR program. The results showed that more than three-forth of the samples considered CSR programs were very positive. Generally, the family’s income increased after followed CSR program. Number of poor families under the poverty line decreased and the number of satisfied family increased. Total income of receiver families of CSR program was higher than nonreceiver families. This research also found there was no significancedifference between subjective wellbeing of receiver and nonreceiver families of CSR program. Factors that affected objective family wellbeing were family size and the benefits of CSR, while the factors that influence subjective family wellbeing were occapation status of wife and the benefits of CSR.